2018
DOI: 10.14336/ad.2017.1127
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Deficient Mice Develop Nephrogenic Diabetes Insipidus

Abstract: Loss-of-function mutations of progranulin are associated with frontotemporal dementia in humans, and its deficiency in mice is a model for this disease but with normal life expectancy and mild cognitive decline on aging. The present study shows that aging progranulin deficient mice develop progressive polydipsia and polyuria under standard housing conditions starting at middle age (6-9 months). They showed high water licking behavior and doubling of the normal daily drinking volume, associated with increased d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…We further found that under the normal conditions, PGRN deficiency in mice had no effects on renal function including the podocyte structure and function, which was consistent with previous studies showing that PGRN knockout mice display normal life expectancy with behavioral deficits and progressive neuropathology but few other recorded phenotypes 26 . Although a recent study has shown that PGRN deficiency mice develop progressive polydipsia and polyuria due to increased drinking behavior and urinary concentrating defect during aging (starting at 6 months), the renal function of aged Grn −/− mice were in the normal range and there were no overt signs of a glomerular or tubular pathology 27 . In this study, we found that there was no significant difference in mitochondrial morphology of podocytes, kidney morphology and urinary albumin excretion between Grn −/− mice (<5 months) and age-matched WT mice under normal condition.…”
Section: Discussionmentioning
confidence: 89%
“…We further found that under the normal conditions, PGRN deficiency in mice had no effects on renal function including the podocyte structure and function, which was consistent with previous studies showing that PGRN knockout mice display normal life expectancy with behavioral deficits and progressive neuropathology but few other recorded phenotypes 26 . Although a recent study has shown that PGRN deficiency mice develop progressive polydipsia and polyuria due to increased drinking behavior and urinary concentrating defect during aging (starting at 6 months), the renal function of aged Grn −/− mice were in the normal range and there were no overt signs of a glomerular or tubular pathology 27 . In this study, we found that there was no significant difference in mitochondrial morphology of podocytes, kidney morphology and urinary albumin excretion between Grn −/− mice (<5 months) and age-matched WT mice under normal condition.…”
Section: Discussionmentioning
confidence: 89%
“…The IntelliCage (NewBehavior AG, Zurich, Switzerland) [ 30 , 51 , [74] , [75] , [76] ] consists of four operant corners, each with two water bottles, sensors, light-emitting-diodes (LEDs) and doors that control the access to the water bottles. The system fits into a large cage (20 × 55 × 38 cm, Tecniplast, 2000P) and allows housing of 16 mice per cage.…”
Section: Methodsmentioning
confidence: 99%
“…The IntelliCage (NewBehavior AG, Zurich, Switzerland) [25,[63][64][65][66] consisted of four operant corners, each with two water bottles, sensors, light-emitting-diodes (LEDs) and doors that controlled the access to the water bottles. The system fit into a large cage (20 cm × 55 cm × 38 cm, Tecniplast, Germany, 2000P) and housed 16 mice per cage.…”
Section: Intellicage Description and Setupmentioning
confidence: 99%